2018
DOI: 10.1097/fjc.0000000000000606
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Ability of Liposomes to Accumulate in the Ischemic Myocardium and Protect the Heart

Abstract: Abstract:Liposomes have the potential to be used for drug delivery. Meanwhile, liposome size may affect their accumulation in the target tissue. We investigated the myocardial accumulation of 2 populations of liposomes (∼70 and 110 nm diameter) during ischemia and their effect on ischemia/reperfusion injury. Isolated rat hearts were subjected to 30 minutes of low-flow ischemia with the liposomes, followed by 30 minutes of liposome-free reperfusion. The liposomes were loaded with the fluorescent dye Nile Red to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…For this purpose, liposomes loaded with fluorescent Nile Red dye were used. Nanoparticle labeling with this hydrophobic dye, which fluoresces preferentially in non-polar environments, is commonly used for bioimaging studies [ 58 , 59 , 60 , 61 ]. Cellular uptake and localization were investigated by fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, liposomes loaded with fluorescent Nile Red dye were used. Nanoparticle labeling with this hydrophobic dye, which fluoresces preferentially in non-polar environments, is commonly used for bioimaging studies [ 58 , 59 , 60 , 61 ]. Cellular uptake and localization were investigated by fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their intrinsic hydrophilic and hydrophobic nature, liposomes have been extensively used to encapsulate a variety of therapeutic agents including proteins, nucleic acid, drugs, and diagnostic agents [ 37 ]. In cardiovascular research, earlier studies showed that liposomal particles can be accumulated in infarcted myocardium [ 38 ], and more recent studies suggest that liposome particles with sizes between 70 to 110 nm are associated with more capabilities to penetrate capillaries and be accumulated in the ischemic myocardium [ 39 ].…”
Section: Nanoparticle Types For Intravascular Imagingmentioning
confidence: 99%
“…The size of LNPs plays an important role in both the LNP biodistribution and LNP performance, such as antitumor effect and gene silencing activity. [1][2][3][4][5][6][7] Generally, small-sized LNPs are desirable for stromal rich tumor tissues, such as pancreatic cancer. On the other hand, 100 nm-sized LNPs can deliver drugs or RNA into the hepatocytes of liver tissues passing through the fenestrae (with an approximate diameter of 100-150 nm).…”
Section: Introductionmentioning
confidence: 99%
“…However, LNPs are produced with a size distribution in spite of size tuning such as extrusion using a polycarbonate lter and ultra-sonication. 1,9 Therefore, a precise LNP size control method is indispensable for understanding the effect of the LNP size on the DDS performance.…”
Section: Introductionmentioning
confidence: 99%